Skeletal Muscle Response to Deflazacort, Dexamethasone and Methylprednisolone - Fappi, Alan (Cells, 2019)
Glucocorticoids represent some of the most prescribed drugs that are widely used in the treatment of neuromuscular diseases, but their usage leads to side effects such as muscle atrophy. However, different synthetic glucocorticoids can lead to different muscle effects, depending upon its chemical formulation. Here, we intended to demonstrate the muscle histologic and molecular effects of administering different glucocorticoids in equivalency and different dosages. Methods: Seventy male Wistar rats distributed into seven groups received different glucocorticoids in equivalency for ten days or saline solution. The study groups were: Control group (CT) saline solution; dexamethasone (DX) 1.25 or 2.5 mg/kg/day; methylprednisolone (MP) 6.7 or 13.3mg/kg/day; and deflazacort (DC) 10 or 20 mg/kg/day. At the end of the study, the animals were euthanized, and the tibialis anterior and gastrocnemius muscles were collected for metachromatic ATPase (Cross-sectional area (CSA) measurement), Western blotting (protein expression of IGF-1 and Ras/Raf/MEK/ERK pathways) and RT-PCR (MYOSTATIN, MuRF-1, Atrogin-1, REDD-1, REDD-2, MYOD, MYOG and IRS1/2 genes expression) experiments. Results: Muscle atrophy occurred preferentially in type 2B fibers in all glucocorticoid treated groups. DC on 10 mg/kg/day was less harmful to type 2B fibers CSA than other doses and types of synthetic glucocorticoids. In type 1 fibers CSA, lower doses of DC and DX were more harmful than high doses. DX had a greater effect on the IGF-1 pathway than other glucocorticoids. MP more significantly affected P-ERK1/2 expression, muscle fiber switching (fast-to-slow), and expression of REDD1 and MyoD genes than other glucocorticoids. Compared to DX and MP, DC had less of an effect on the expression of atrogenes (MURF-1 and Atrogin-1) despite increased MYOSTATIN and decreased IRS-2 genes expression. Conclusions: Different glucocorticoids appears to cause muscle atrophy affecting secondarily different signaling mechanisms. MP is more likely to affect body/muscles mass, MEK/ERK pathway and fiber type transition, DX the IGF-1 pathway and IRS1/2 expression. DC had the smallest effect on muscle atrophic response possibly due a delayed timing on atrogenes response.